Oxysarcodexia Townsend, 1917 (Diptera: Sarcophagidae)—a centennial conspectus - de Souza, Carina Mara; Pape, Thomas; Thyssen, Patricia Jacqueline (Zootaxa, 2020)
A taxonomic conspectus is presented for the genus Oxysarcodexia Townsend, 1917, which is one of the most species-rich genera of New World flesh flies. It has its center of diversity in the Neotropical Region, with some species reaching into the Nearctic and a few species introduced to the Australasian and Oceanian Regions. Species within this genus are primarily dung-breeders, but some species have also been bred from vertebrate carcasses. Oxysarcodexia is defined and diagnosed, and a diagnosis, distributional data and known biological data are provided for each species together with figures of the habitus and male terminalia. Oxysarcodexia currently comprises 91 valid species, including six species newly described herein: O. alectoris sp. n. (French Guiana), O. angulosa sp. n. (Costa Rica), O. ariozanoi sp. n. (Brazil), O. graminifolia sp. n. (Colombia and Ecuador), O. maiae sp. n. (Ecuador), and O. rimata sp. n. (Ecuador). Two nominal species based on a male holotype, Oxysarcodexia bomplandi (Hall, 1937) and O subsericans (Walker, 1858), were left unidentified pending examination of their terminalia. Four nominal species, O. aureiceps (Macquart, 1855), O. dorisae Dodge, 1965, O. flavifrons (Macquart, 1846) and O. neivae Mattos, 1919, all described solely based on females, are considered of uncertain status pending a comprehensive study of females of this genus. Asioboettcheria Verves, 2001 is proposed as a junior synonym of Oxysarcodexia Townsend, 1917, syn. n., Oxysarcodexia cuernavaca Dodge, 1966 is proposed as a junior synonym of O. ventricosa (Wulp, 1895), syn. n., and Stackelbergeola papei Nandi, 1994 is proposed as a junior synonym of O. thornax (Walker, 1849), syn. n. A lectotype is designated for Sarcophaga varia Walker, 1836 [= O. varia (Walker, 1836)]. The newly-described O. ariozanoi and O. maiae are included in the “xon group” (former “Xarcophaga group”). New country-level distributional records are provided for O. adunca Lopes, 1975 (Ecuador), O. berlai Lopes, 1975 (Peru), O. cocais Carvalho-Filho, Sousa & Esposito, 2017 (Argentina), O. insolita Lopes, 1946 (Ecuador), O. jamesi Dodge, 1968 (Costa Rica), O. marina (Hall, 1938) (Brazil), O. nitida Soares & Mello-Patiu, 2010 (Ecuador), O. notata Soares & Mello-Patiu, 2010 (Brazil and Ecuador), and O. terminalis (Wiedemann, 1830) (Paraguay).